A MoO3 composite TiO2 hydrogen-sensitive material and preparation method thereof
By combining TiO2 and MoO3, an n-n heterojunction is formed, and the hydrogen sensing performance is improved, the existing hydrogen sensor response is not sensitive enough and the stability is poor at room temperature, and efficient and stable hydrogen detection is achieved.
Patent Information
- Application Number
- CN202211474042.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-23
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2042-11-23
AI Technical Summary
The existing hydrogen sensors at room temperature are not sensitive enough, have poor stability, and are difficult to achieve efficient detection.
By combining TiO2 with MoO3, an n-n heterojunction is formed, and the hydrogen sensing performance is improved. Specific methods include hydrothermal preparation of TiO2 and MoO3 composites and annealing treatment to form a multi-faceted porous three-dimensional structure.
High sensitivity detection of hydrogen at room temperature is achieved, with short response time, high response value, good material stability, and small decrease in response value for long-term use.
Smart Images

Figure CN116199261B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the preparation and application fields of hydrogen-sensitive sensing materials, and in particular to a MoO3 composite TiO2 hydrogen-sensitive material and a preparation method thereof. Background Art
[0002] Among many new energy sources, hydrogen (H2) has long been of concern to people because of its clean and pollution-free characteristics. At the same time, hydrogen is also an important industrial gas, and it has an irreplaceable position in modern industrial fields such as metallurgy, fine organic synthesis, and aerospace. Because H2 has the physical properties of being colorless and odorless, it cannot be directly perceived by the naked eye. When the concentration of H2 in the air is >4%, there is a potential risk of explosion. Therefore, there are safety hazards that cannot be ignored during the storage, transportation and application of H2. Therefore, in order to prevent the leakage of H2, it is urgent to develop a room temperature hydrogen sensor to detect H2.
[0003] Among many sensors, resistive metal oxide semiconductor hydrogen sensors (MOGS) have been widely studied at this stage. MOGS has the advantages of simple structure, high sensitivity, low cost, and long service life. It has good application prospects and can meet the actual requirements of H2 detection. Its response principle is that the metal semiconductor first contacts oxygen in the air to form oxygen species on the surface, which increases the ground state resistance of the sensor. Then H2 reacts with the oxygen species on the surface to release electrons, which reduces the resistance of the sensor. However, among the existing sensors for hydrogen detection at room temperature, semiconductor resistive hydrogen sensors still have unsatisfactory shortcomings such as insufficient response sensitivity and poor stability. Therefore, achieving efficient detection of H2 at room temperature is a difficult problem that needs to be addressed.
[0004] TiO2 is an n-type semiconductor metal oxide. The preparation process of TiO2 is simple. It has good chemical stability and biocompatibility and is widely used in photocatalytic hydrogen production, photocatalytic reduction, lithium batteries, gas sensing and other fields. Although TiO2 metal semiconductor sensors have been widely studied, due to the low specific surface area and material structure factors, the original TiO2 sensors generally have the disadvantages of narrow H2 detection range, low response, poor gas selectivity, etc., which are not enough for actual hydrogen detection. In order to detect gas at lower concentrations and lower operating temperatures, it is necessary to develop efficient TiO2-based gas sensors. It is a widely recognized fact that material structure plays a vital role in gas sensing detection, just like the material. Ordered mesoporous TiO2 is a good gas-sensitive material, and this porous structure is conducive to the diffusion of gas.
[0005] Metal-organic frameworks (MOFs) are crystalline porous materials composed of organic and inorganic non-metallic components. Due to their high specific surface area, special porosity and diverse structures, MOFs have become attractive nanomaterials. The applications of MOFs have been explored in catalysis, separation and adsorption, gas sensing, biosensing and supercapacitors.
[0006] MIL-125 has a huge surface area and stable structural features. Therefore, it is considered to be an attractive sacrificial template for obtaining metal oxide nanostructures by pyrolysis.
[0007] In this study, MIL-125 was synthesized by a hot solvent method and annealed to form a multifaceted porous three-dimensional structure of TiO2. When used as a gas sensor, the prepared TiO2 had a maximum response of 9.2 to 1000ppm H2 at 30 degrees Celsius. The TiO2 nanostructure has a fast response / recovery time and high linearity, and has the best selectivity for H2 gas. Therefore, the multifaceted porous three-dimensional structure of TiO2 prepared in the present invention has the potential to become an excellent hydrogen-sensitive sensing material. Summary of the invention
[0008] The purpose of the present invention is to modify the existing TiO2. The nn heterojunction formed between TiO2 and MoO3 plays a major role in improving the hydrogen sensing performance.
[0009] The present invention achieves the above technical objectives through the following technical means:
[0010] (1) Preparation of TiO2 precursor: Weigh terephthalic acid, anhydrous methanol, anhydrous N, N-dimethylformamide (DMF) and tetrabutyl titanate (Ti(OC4H9)4) and put them into a beaker and stir to mix them evenly. Transfer the stirred solution to a reactor for hydrothermal reaction. Then cool the product to room temperature, collect the obtained white precipitate, wash it with anhydrous methanol several times, and put it in an oven to dry.
[0011] (2) Preparation of TiO2: Weigh the pre-hydrothermal white powder and put it into a porcelain boat. Place the porcelain boat in a muffle furnace and calcine it at 400°C in an air atmosphere for 10 h. After natural cooling, collect the TiO2 white powder.
[0012] (3) Preparation of TiO2 / MoO3 composite precursor: Similarly, weigh terephthalic acid, anhydrous methanol, anhydrous N, N-dimethylformamide (DMF), tetrabutyl titanate (Ti(OC4H9)4) and ammonium molybdate tetrahydrate and put them into a beaker and stir to mix them evenly. The stirred solution is transferred to a reactor for hydrothermal reaction. The product is then cooled to room temperature, the obtained white precipitate is collected, washed with anhydrous methanol several times, and dried in an oven to obtain a white powder.
[0013] (4) Preparation of TiO2 / MoO3 composite: Weigh the pre-hydrothermal white powder and put it into a porcelain boat. Place the porcelain boat in a muffle furnace and calcine it at 400°C in air atmosphere for 10 h. After natural cooling, collect the black powder of TiO2 / MoO3 composite.
[0014] Furthermore, in step (3), the ratio of terephthalic acid, anhydrous methanol, anhydrous N, N-dimethylformamide (DMF), and tetrabutyl titanate (Ti(OC4H9)4) is 3.15 g: 7 ml: 63 ml: 1.635 g; in the white powder, Mo 6+ / Ti 4+ The molar ratios were 5 / 95, 7 / 93 and 9 / 91 respectively.
[0015] The sensing material is used in hydrogen gas sensing at room temperature. The specific sensing response test is as follows:
[0016] Take 5 mg of the prepared black powder and grind it with pine alcohol to form a uniform paste. Then use a pipette to apply 5 μL of the obtained slurry on the surface of the alumina substrate (i.e., the pt-coated alumina electrode) to form a thin layer. In order to improve the stability of the sensing layer, the electrode sheet was annealed at 300 ° C for 2 hours to obtain the test electrode.
[0017] Compared with the conventional metal oxide semiconductor hydrogen sensing materials on the market, which have high response temperature or require noble metal doping for room temperature response, the present invention has a low cost and does not require noble metal doping while lowering the response temperature; and the synthesis method is simple, and the synthesized sample has a porous and multifaceted three-dimensional structure through only hydrothermal and annealing treatment, and has a large specific surface area, providing more active sites for gas adsorption. The nn heterojunction formed by the composite further improves the morphology and forms a large number of oxygen vacancies, which reduces the response temperature of the material while also improving the response speed of the material (1000ppm, 36s) and the response value. The material has good repeatability and is also very stable at room temperature. After being placed for 45 days, the response value only drops by less than 10%, and it has good selectivity for hydrogen. Therefore, the present invention is a room temperature hydrogen sensing material with great potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1These are the XRD spectra of the pure phase TiO2 prepared in Example 2 of the present invention and the 5% TiO2 / MoO3, 7% TiO2 / MoO3, and 9% TiO2 / MoO3 composites prepared in Example 4.
[0019] Figure 2 The SEM spectrum of the 7% TiO2 / MoO3 composite prepared in Example 4 of the present invention; (a) low magnification, (b) high magnification.
[0020] Figure 3 This is the XPS spectrum of the 7% TiO2 / MoO3 nanosheets prepared in Example 4 of the present invention; Figure 3 (a) is the peak of Ti element, Ti 2p 3 / 2 The combined peak is 458.1 eV, which is the Ti 2p 1 / 2 The binding energy of the peak is 463.8 eV. Ti 2p 3 / 2 The peak value is attributed to Ti 4+ . Figure 3 (b) It can be seen that Mo 3d 5 / 2 and Mo3d 3 / 2 The binding energies of are 232.9 and 236.0 eV, respectively. Figure 3 (c) shows the lattice oxygen (O L , 531.2eV) and adsorbed oxygen (O V , 531.1 eV), indicating that there are 30.2% oxygen vacancies in the composite.
[0021] Figure 4 Dynamic response curves of pure TiO2 phase prepared in Example 2 of the present invention and 5% TiO2 / MoO3, 7% TiO2 / MoO3, and 9% TiO2 / MoO3 composites prepared in Example 4 to hydrogen at room temperature (30°C).
[0022] Figure 5 The dynamic response curves of the pure phase TiO2 prepared in Example 2 of the present invention and the 5% TiO2 / MoO3, 7% TiO2 / MoO3, and 9% TiO2 / MoO3 composites prepared in Example 4 to hydrogen at room temperature (30°C).
[0023] Figure 6 This is a test of the selectivity of 7% TiO2 / MoO3 prepared in Example 4 of the present invention to different gases at room temperature (30°C).
[0024] Figure 7 This is a repeatability test of the 7% TiO2 / MoO3 prepared in Example 4 of the present invention.
[0025] Figure 8 This is a response value stability test of 7% TiO2 / MoO3 prepared in Example 4 of the present invention. DETAILED DESCRIPTION
[0026] Embodiment 1:
[0027] Preparation of TiO2 precursor: 3.15g terephthalic acid, 7mL anhydrous methanol, 63mL anhydrous N, N-dimethylformamide (DMF) and 1.635g tetrabutyl titanate (Ti(OC4H9)4) were placed in a 100ml beaker, stirred to mix evenly, and the stirred solution was transferred to a 100ml reactor and kept in an oven at 150°C for 48h. The product was then cooled to room temperature, the white precipitate was collected, washed with anhydrous methanol several times, and dried in an oven for 24h.
[0028] Embodiment 2:
[0029] Preparation of TiO2: Put the white powder into a porcelain boat, then put the porcelain boat into a muffle furnace at 2℃min -1 The temperature was raised to 400°C at a speed of 100 °C and kept at this temperature for 10 hours. After natural cooling, the white TiO2 powder was collected.
[0030] Embodiment 3:
[0031] Preparation of composite precursor: 3.15 g terephthalic acid, 7 mL anhydrous methanol, 63 mL anhydrous N, N-dimethylformamide (DMF), 1.635 g tetrabutyl titanate (Ti(OC4H9)4) and ammonium molybdate tetrahydrate were placed in a 100 ml beaker. 6+ / Ti 4+ The molar ratios of the reaction mixture were 5 / 95, 7 / 93, and 9 / 91, and the amounts of ammonium molybdate tetrahydrate added were 0.045 g, 0.063 g, and 0.084 g, respectively. The mixture was stirred to make it uniformly mixed, and the stirred solution was transferred to a 100 ml reactor and kept in an oven at 150°C for 48 hours. The product was then cooled to room temperature, and the white precipitate was collected, washed with anhydrous methanol several times, and dried in an oven for 24 hours.
[0032] Embodiment 4:
[0033] Preparation of TiO2 / MoO3 composite: white powder was placed in a porcelain boat, and then the porcelain boat was placed in a muffle furnace at 2℃min -1 The temperature was raised to 400°C at a speed of 100 °C and kept at this temperature for 10 hours. After natural cooling, black powder was collected. The obtained powders were divided into three groups, namely 5% TiO2 / MoO3, 7% TiO2 / MoO3, and 9% TiO2 / MoO3.
[0034] Tests and Results
[0035] The test method for hydrogen gas sensing performance provided by the present invention is as follows:
[0036] Take 5 mg of the prepared TiO2 powder and grind it with pine oil to form a uniform paste. Then use a pipette to apply 5 μL of the obtained slurry on the surface of the alumina substrate (i.e., pt-coated alumina electrode) to form a thin layer. In order to improve the stability of the sensing layer, the electrode sheet is annealed at 300°C for 2 hours. The test gas H2 is in a high-purity steel cylinder, with a ratio of 5000ppm H2 standard gas (0.5% H2, 99.5% N2) and high-purity air. The H2 standard gas is mixed with air by setting a program to control the gas mixer to obtain a H2 gas with a concentration of 200ppm-1000ppm. The hydrogen sensing performance at room temperature is measured with dynamic airflow in a four-channel tester. The test process is as follows: first, pure air is introduced until the resistance value of the test electrode stabilizes to R a Then, a specific concentration of mixed H2 is introduced and the resistance change is recorded until the resistance drops to a stable value. g After the mixed gas is turned off, continue to pass air until the resistance value rises back to another stable value. This test process is repeated to test the response value of the sample to different concentrations of H2, and finally the dynamic response-recovery curve of the sample is obtained. The response value, response / recovery time, stability and other calculation parameters of the gas sensor are analyzed by the response-recovery curve.
[0037] Figure 1 The XRD diffraction patterns of TiO2 / MoO3 composite materials and pure phase TiO2 are shown in Figure 1. First, the XRD spectra ( Figure 1 ) shows that the diffraction peaks of the obtained TiO2 microstructure can be well indexed with the anatase titanium dioxide standard card (PDF#21-1272). There is no peak of rutile titanium dioxide, indicating that pure anatase titanium dioxide is generated. The (021) peak of MoO3 appears in the composite. With the increase of Mo doping, the diffraction peak becomes more obvious, which can be indexed as the orthorhombic structure α-MoO3 standard card (JCPDS No.050508). And after molybdenum compounding, all diffraction peaks are more obvious, indicating that the crystallinity of the composite is higher. There are no obvious impurities in the diffraction peaks in the figure. The test results of XRD show that pure TiO2 and TiO2 / MoO3 composite materials were successfully prepared.
[0038] Figure 2The following are low-magnification and high-magnification SEM images of 7% TiO2 / MoO3. The results of SEM characterization can be summarized as follows. First, in the low-magnification image, the prepared 7% TiO2 / MoO3 is a three-dimensional octahedral structure with uniform distribution and no large-scale agglomeration. The MoO3 nanoparticles are distributed on the surface of TiO2 with an average diameter of 50nm. Secondly, in the high-magnification image, it can be seen that the TiO2 cake-shaped three-dimensional structure is aggregated by particles with an average diameter of 50nm, forming a porous and multi-faceted three-dimensional structure with an average diameter of about 750nm and a thickness of 250nm. The synthesized porous and multi-faceted structure can provide a large number of active sites, which is beneficial for the detection of hydrogen.
[0039] Figure 3 XPS spectrum of 7% TiO2 / MoO3. Figure (a) shows the peak of Ti element, Ti 2p 3 / 2 The combined peak is 458.1 eV, which is the Ti 2p 1 / 2 The binding energy of the peak is 463.8 eV. Ti 2p 3 / 2 The peak value is attributed to Ti 4+ Figure (b) shows that Mo3d 5 / 2 and Mo3d 3 / 2 The binding energies of lattice oxygen (O L , 531.2eV) and adsorbed oxygen (O V , 531.1eV), indicating that the composite has 30.2% oxygen vacancies, which is beneficial to the adsorption of oxygen at room temperature and can improve the detection performance of hydrogen. The XPS results further demonstrate the previous XRD conclusions, indicating that TiO2 / MoO3 was successfully prepared.
[0040] Figure 4 , Figure 5The dynamic response curves and response value change curves of pure TiO2 and 5% TiO2 / MoO3, 7% TiO2 / MoO3, and 9% TiO2 / MoO3 composites, respectively, show the following points: (1) The resistance of the TiO2 / MoO3-based sensor decreases after H2 is introduced, and increases after air is introduced, indicating that its response to hydrogen at room temperature is still n-type response, and the composite of MoO3 does not change the chemical properties of TiO2. (2) It is known that 7% Mo doping is the best composite amount, which improves the response to H2 compared to the pure sample, and the response value increases by 4.5 times at 1000ppm. The response characteristics at 1000ppm are linear responses. When the H2 concentration exceeds 1000ppm, the response value increases significantly, especially when the H2 concentration is 4000ppm, the response value is 1200, and the response increases by 40 times. Its high response is due to the combined effects of the porous and multifaceted structural characteristics, heterojunction effect, and a large number of oxygen vacancies, which increases the oxygen adsorption at room temperature and greatly increases the resistance in the air at room temperature. (3) When Mo doping reaches 9%, it will inhibit the response of the raw material to H2.
[0041] Figure 6 The selectivity of 7% TiO2 / MoO3 sample to hydrogen, carbon monoxide and propylene at different concentrations is shown in the figure. From the curve, it can be seen that the selectivity response of 7% TiO2 / MoO3 material to carbon monoxide and propylene at any concentration is poor. At 1000ppm, the response value of 7% TiO2 / MoO3 to H2 is 3 times and 3.5 times of the response value to carbon monoxide and propylene respectively. The results show that 7% TiO2 / MoO3 has selectivity to H2.
[0042] Figure 7 This is the repeatability test of the 7% TiO2 / MoO3 composite. It can be seen that the sample has good repeatability.
[0043] Figure 8 This is a stability test of 7% TiO2 / MoO3. It can be seen from the dynamic response-recovery characteristic curve to H2 that the 7% TiO2 / MoO3 sample has good recyclability to H2. On this basis, its long-term stability was tested, and the results are shown in the figure. It can be seen that the sample can still maintain a high response value after 40 days, and its response value has dropped by 10%. It can be considered that the 7% TiO2 / MoO3 sample not only has good recyclability and a response value that changes with the detection concentration, but also has relatively long-term stability.
Claims
1. A method for preparing a MoO3 composite TiO2 hydrogen-sensitive material, characterized in that: The specific steps are as follows: (1) Preparation of TiO2 / MoO3 composite precursor: Weigh terephthalic acid, anhydrous methanol, anhydrous N,N-dimethylformamide, tetrabutyl titanate and ammonium molybdate tetrahydrate, put them into a beaker and stir them to mix them evenly. Transfer the stirred solution to a reactor for hydrothermal reaction. Then cool the product to room temperature, collect the obtained white precipitate, wash it with anhydrous methanol several times, and put it into an oven to dry to obtain a white powder. (2) Preparation of TiO2 / MoO3 composite: Weigh the pre-hydrothermal white powder and put it into a porcelain boat. Place the porcelain boat in a muffle furnace and calcine it at 400°C in air atmosphere for 10 h. After natural cooling, collect the black powder of TiO2 / MoO3 composite.
2. The method for preparing a MoO3 composite TiO2 hydrogen-sensitive material according to claim 1, characterized in that: In step (1), the ratio of terephthalic acid, anhydrous methanol, anhydrous N, N-dimethylformamide (DMF), and tetrabutyl titanate (Ti(OC4H9)4) is 3.15 g: 7 ml: 63 ml: 1.635 g; in the white powder, Mo 6+ / Ti 4+ The molar ratios were 5 / 95, 7 / 93 and 9 / 91 respectively.
3. The method for preparing a MoO3 composite TiO2 hydrogen-sensitive material according to claim 2, characterized in that: In white powder, Mo 6+ / Ti 4+ The molar ratio is 7 / 93.
Citation Information
Patent Citations
Preparation method of nano porous hollow cage-shaped titanium oxide loaded with different metals
CN109261146A
Preparation method of novel ammonia gas sensor based on MOFs material
CN113433172A